The Structure and growth pattern of agro-industry of African countries (UNIDO ViennaAT, 2013)
Analyses the agro-industrial performance of selected countries in Africa using descriptive statistical methods such as ratios, shares and averages. Analyses a number of economic indicators such as value added, output, employment in the sectors in some countries, value of agro-industrial exports and value of agricultural machinery imports.
Keywords: AGROINDUSTRY